CITRA PENDAKWAH â€œGOOD LOOKINGâ€ : Melihat dari Perpektif Mahasiswa Muslim - Athoâ€™ilah Aly Najamudin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Abstract This article wants to see good looking preachers from the perspective of students, especially with a phenomenological approach. The understanding of some people assumes that good looking in the image of the preacher is strongly influenced by the power of the media. Such an image with the intention of influencing the perception of people or society that has brought social and cultural changes. Here the researcher displays the empathy of handsome preachers namely, Ustad Hannan Attaqi, Habib Husein Jaffar Al-Hadar, Gus Miftah and Ustad Solmed. The object of the research is the postgraduate student of Anthropology at Gajah Mada University. The research wants to show that good looking is the main social capital for preachers in explaining da'wah narratives. The power of modernity is forming the image of the preacher through the mediatization process.